Knowledge and practice of diabetic foot care and the associated factors for practice among patients attending outpatient clinics in Kuala Terengganu, Terengganu - Ismail, Nurul Izzatul Aisyah (2020)
Aim of study To determine the proportion of good knowledge and practice of diabetic foot care and its associated factors for good practice among patients attending outpatient clinics in Kuala Terengganu, Terengganu. Methodology A cross sectional study was conducted involving 383 diabetic patients attending outpatient clinics in Kuala Terengganu who fit the inclusion and exclusion criteria and they were recruited using systematic sampling. A self-developed and preliminary tested administered questionnaire was administered and consisted of 3 domains assessing the sociodemographic data, knowledge and practices about diabetic foot care. Each knowledge and practice domain consist of 15 questions. Their score is classified as good knowledge, poor knowledge, good practice and poor practice. The score of more than 70% is considered as good knowledge and practice for both domain. Results Median age of the respondents was 60.0 (IQR 12). 70.2% of the respondent had good knowledge regarding diabetic foot care but only 58.7% had good practice about diabetic foot care. Mean (SD) for knowledge score was 11.3 (2.40) and 22.1 (4.39) for practice. The good practice of diabetic foot care has significant statistical association with sex (p=0.014), race (p=0.028) and level of knowledge of diabetic foot care (p<0.001). Conclusion: The level of knowledge and practice regarding diabetic foot care still under optimized among diabetic patients that attending outpatient clinics in Kuala Terengganu. Sex, race and level of good knowledge has significant association with good practice of diabetic foot care. The action need to be taken by healthcare providers in emphasizing the importance of good diabetic foot care practice as preventive measure to reduce the disease burden to the patients and healthcare system.